Структурный синтез модели зрелости SPICE Integration - Рубин, Эдуард Ефимович; Годлевский, Михаил Дмитриевич; Бараш, Виталий Сергеевич (НТУ "ХПИ", 2015)
Рассматриваются подходы к улучшению качества процесса разработки программного обеспечения на основе моделей зрелости CMMI и SPICE. Проводится их сравнительный анализ и предлагается подход к формированию гибкой структуры модели зрелости SPICE, которая учитывает недостатки существующих моделей. Реализация гибкой структуры осуществляется путём структурно-параметрического синтеза модели зрелости SPICE Integration.

Nowadays lots of IT companies face the plethora of problem on their way to the successful ending of their projects. Even if they have enough time, money and resources (e.g. people, technical equipment, etc.), it is quite challenging for them to deliver their project on time, within budget and with appropriate level of quality. Hence, there have been created several approaches in order to improve quality of processes that are involved into software development. The most popular branch of them is software process improvement (SPI). The main representative of SPI i s maturity models such as CMMI and SPICE (ISO/IEC TR 15504). There has been provided a comparison of them and come up a means of composing a flexible structure of the maturity model SPICE that takes into account drawbacks of existing models. For instance, CMMI does not provide companies with freedom in decision-making – it says to companies what they have to achieve and complete despite their goals, uniqueness of their spheres of expertise and so on. Talking about SPICE, it does not provide companies with road maps to accomplish the best quality of their work that they need to. Therefore, there have been described approaches of improving quality of software development process that are based on the maturity models and proposed a procedure of structural synthesis of the maturity model SPICE Integration.
Structural synthesis of the maturity model SPICE Integration
Keywords: процесс разработки; программное обеспечение; ПО; жизненный цикл; модель зрелости; quality; software development process; analysis